A Framework for Determining the Return on Investment of Simulation-Based Training in Health Care - Hatim Bukhari MS; Pamela Andreatta PhD; Brian Goldiez PhD; Luis Rabelo PhD (SAGE Publishing, 2017)
This article describes a framework that has been developed to monetize the real value of simulation-based training in health care. A significant consideration has been given to the incorporation of the intangible and qualitative benefits, not only the tangible and quantitative benefits of simulation-based training in health care. The framework builds from three works: the value measurement methodology (VMM) used by several departments of the US Government, a methodology documented in several books by Dr Jack Phillips to monetize various training approaches, and a traditional return on investment methodology put forth by Frost and Sullivan, and Immersion Medical. All 3 source materials were adapted to create an integrated methodology that can be readily implemented. This article presents details on each of these methods and how they can be integrated and presents a framework that integrates the previous methods. In addition to that, it describes the concept and the application of the developed framework. As a test of the applicability of the framework, a real case study has been used to demonstrate the application of the framework. This case study provides real data related to the correlation between the pediatric patient cardiopulmonary arrest (CPA) survival rates and a simulation-based mock codes at the University of Michigan tertiary care academic medical center. It is important to point out that the proposed framework offers the capability to consider a wide range of benefits and values, but on the other hand, there are several limitations that has been discussed and need to be taken in consideration.